2019
DOI: 10.12697/akut.2018.24.08
|View full text |Cite
|
Sign up to set email alerts
|

The effect of isometric handgrip training on blood pressure

Abstract: The aim of this study was to determine the effect of single-bout isometric handgrip training on systolic (BPS) and diastolic blood pressure (BPD). Healthy normotensive (BP<120/80 mmHg) (n=6) and prehypertensive (BPS 120–139 mmHg and/or BPD 80–89 mmHg) (n=6) women with mean age of 47.3±14.0 years, who did not take antihypertensive medicine, participated in the study. Blood pressure (BP) was measured with aneroid sphygmomanometer Riester Precisa N (Germany). Thereafter with the JAMAR hydraulic hand dynamomete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 19 publications
0
9
0
1
Order By: Relevance
“…Keterlibatan massa otot yang lebih kecil selama latihan isometrik (unilateral vs bilateral dan ekstremitas atas dan ekstremitas bawah) menghasilkan penurunan tekanan darah yang lebih tinggi (Lopes et al, 2018). Tekanan darah dan respons detak jantung terhadap latihan isometrik dipengaruhi oleh kekuatan kontraksi, ukuran otot yang berkontraksi dan lamanya waktu yang digunakan (Piikmann & Reisberg, 2018…”
Section: Pendahuluanunclassified
“…Keterlibatan massa otot yang lebih kecil selama latihan isometrik (unilateral vs bilateral dan ekstremitas atas dan ekstremitas bawah) menghasilkan penurunan tekanan darah yang lebih tinggi (Lopes et al, 2018). Tekanan darah dan respons detak jantung terhadap latihan isometrik dipengaruhi oleh kekuatan kontraksi, ukuran otot yang berkontraksi dan lamanya waktu yang digunakan (Piikmann & Reisberg, 2018…”
Section: Pendahuluanunclassified
“…Thirteen studies reported on the acute changes in resting blood pressure at least 1 min following a single bout of isometric handgrip exercise (van Assche et al, 2017; Bentley & Thomas, 2016, 2018; Goessler et al, 2016; McGowan et al, 2012; Millar, MacDonald, et al, 2009, 2011; Murugan & Sk, 2018; Patel et al, 2015; Piikmann & Reisberg, 2018; Silva et al, 2018; Souza et al, 2018; Teixeira et al, 2018) (Table 1). All studies were within‐subject experiments.…”
Section: Methodsmentioning
confidence: 99%
“…However, the order was not randomized (Murugan & Sk, 2018). The remaining four studies only had an isometric handgrip exercise condition (Bentley & Thomas, 2016; McGowan et al, 2012; Patel et al, 2015; Piikmann & Reisberg, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Less muscle mass involvement during isometric exercise (unilateral vs. bilateral and upper and lower extremity) results in a higher reduction in blood pressure (Lopes et al, 2018). Blood pressure and heart rate response to isometric exercise are influenced by the strength of contractions, the size of the muscles contracting and the length of time used (Piikmann & Reisberg, 2019).…”
Section: Effect Of Isometric Handgrip Exercie On Blood Pressurementioning
confidence: 99%